2018
DOI: 10.1115/1.4041134
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Geometric Parameters on the Injection Characteristic of the High Pressure Common-Rail Injector

Abstract: According the actual structure and working principle of a fuel injector to build a model of the common-rail injector, including the control valve, the solenoid valve, and the needle valve of the injector. The model includes the leakage model for the control piston and needle valve that takes into account increasing leakage at high pressure. The performance of the fuel injector is investigated using a one-dimensional numerical model. Analyzing the effect of the system and structure parameters including common-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, when a large clearance leakage occurs, in order to increase the injection quantity by 13%240%, the fuel leakage increases threefold. Wang et al 10 pointed out that the leakage at the needle valve and the control piston coupling greatly affected the injection characteristics of the common rail injector, and the transient leakage characteristics of the fuel under high pressure should be considered during the construction of the numerical model. Catania and Ferrari 11 found that the higher rail pressure would lead to a decrease in the overall volumetric efficiency of the fuel pump without changing the rotational speed, which is related to the increase of fuel leakage rate and the fuel expansion in the clearance volume.…”
Section: Introductionmentioning
confidence: 99%
“…However, when a large clearance leakage occurs, in order to increase the injection quantity by 13%240%, the fuel leakage increases threefold. Wang et al 10 pointed out that the leakage at the needle valve and the control piston coupling greatly affected the injection characteristics of the common rail injector, and the transient leakage characteristics of the fuel under high pressure should be considered during the construction of the numerical model. Catania and Ferrari 11 found that the higher rail pressure would lead to a decrease in the overall volumetric efficiency of the fuel pump without changing the rotational speed, which is related to the increase of fuel leakage rate and the fuel expansion in the clearance volume.…”
Section: Introductionmentioning
confidence: 99%
“…As the “brain” and “heart” of a high‐speed and high‐power diesel engine, the high‐pressure common rail injection system enables a precise adjustment of the fuel injection to increase the output power of a diesel engine, improve fuel economy, and reduce the emission of nitrogen oxides and particulate matter significantly 2–4 . As the core component of a high‐pressure common rail injection system, a fuel injector represents the highest technology level and development difficulty for the common rail system, and it exerts an important impact on the power performance, fuel economy, and emission control of diesel engines 5,6 . The strong flow recirculation and local depression inside a fuel injector provide favorable conditions for the occurrence of cavitation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] As the core component of a high-pressure common rail injection system, a fuel injector represents the highest technology level and development difficulty for the common rail system, and it exerts an important impact on the power performance, fuel economy, and emission control of diesel engines. 5,6 The strong flow recirculation and local depression inside a fuel injector provide favorable conditions for the occurrence of cavitation. 7 Cavitation, which exerts a facilitating effect on the atomization of the fuel, mainly occurs inside injector nozzles and control valves.…”
Section: Introductionmentioning
confidence: 99%
“…As the core component of the high-pressure common rail system, the injector has the highest precision, the most constituent parts, the worst working environment, and is prone to wear and tear. It represents the highest technical content and development difficulty of the high-pressure common rail system, and its performance directly affects the performance of the entire diesel engine [11].…”
Section: Introductionmentioning
confidence: 99%